Exploring Marketing Strategies of Deaf Employing Coffee Shops in the Greater Jakarta (Case Study of Sunyi Coffee and Difabis Coffee) - Rizka Astari Rahmatika (Universitas Batanghari, 2022)
In a world that gradually promotes inclusive workplace and business practice, Sunyi Coffee and Difabis Coffee have become businesses which employ People with Disability (PwD) as their core employees. Aside from embodying both coffee shops’ benevolent missions, this strategy also serves as a part of a marketing strategy to maneuver in a highly competitive, almost saturated coffee shop industry in Greater Jakarta. This research was conducted to explore how both coffee shops tailor different strategies and offerings around the theme of disability employment. This study used a descriptive qualitative method with a case study approach through a variety of data collection, such as interviews with customers, direct observation, online interviews with the founders, websites, social media, and relevant academic literature. Using Porter’s Five Forces Model, this study reveals that the coffee shop industry in Indonesia is highly competitive, with a high level of substitutes, new entrants, and buyers’ bargaining power. An analysis of the 7p marketing mix also shows people and place as the two most essential aspects for Sunyi Coffee and Difabis Coffee. Therefore, to establish a less contested market for themselves, both coffee shops create four action strategies (Eliminate-Reduce-Raise-Create) around these aspects, with Sunyi Coffee pursuing a differentiation strategy and Difabis Coffee focusing more on cost leadership.